An overview of characteristics of municipal solid waste fuel in China: Physical, chemical composition and heating value - Zhou, Hui; Meng, AiHong; Long, YanQiu; Li, QingHai; Zhang, YanGuo (Renewable & sustainable energy reviews, 2014)
In this paper, the characteristics of physical and chemical composition of municipal solid waste (MSW) in China were reviewed and the statistical indexes, namely mean value, standard deviation, coefficient of variation, and t-test, were applied to analyze the physical composition, proximate, ultimate analysis, and heating value. Listed in decreasing sequence, the physical components of Chinese MSW are in food residue, non-combustibles, plastics, paper, textiles, wood waste, and rubber. In food residue, the average elementary hydrogen (H), oxygen (O) and nitrogen (N) content varied greatly with samples and the chlorine (Cl) and moisture contents were extraordinarily high. While conversely, the components of wood waste were simple and different components displayed little disparity in characteristics. The elemental compositions of paper and textiles were also simple. The properties of chlorine-free plastics (polyethylene, polypropylene and polystyrene) were consistent, with high volatile matter, carbon (C) and H content. The mean higher heating value (HHV) of polrvinyl chloride (PVC) was about a half of that of chlorine-free plastics, because the Cl content of PVC was approximate 50%. It suggested that plastics with or without chlorine should be separated as possible. The HHV of different rubbers varied sharply, from 21,812 to 38,868kJ/kg. A model was proposed to predict the proximate and ultimate analysis and heating value from physical composition, in which the PVC fraction in plastics and the supplementary moisture coefficient were introduced. The results showed that the predicted results fitted well with the measured ones.